2010
DOI: 10.1002/app.32698
|View full text |Cite
|
Sign up to set email alerts
|

Properties of compression‐molded plates made from wood powders impregnated with liquefied wood‐based novolak‐type phenol‐formaldehyde resins

Abstract: Novolak-type phenol-formaldehyde (PF) resins with solution form were prepared by reacting phenol-liquefied Cryptomeria japonica (Japanese cedar) wood with formalin in the presence of methanol. Wood powders of Albizzia falcate (Malacca albizzia) impregnated with these resins were air dried followed by an oven-dried at 60 C. DSC analysis showed the PF resin existing in wood powders could be melted, and could be cured if hexamine was mixed and heated at high temperature. Compressionmolded plates made with PF resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Comparing the microwave dried impregnated OPTCL to Rubber wood still a large gap for impact strength is observed. 24 This big gap is attributed to the brittleness of the PF resin which has been fully loaded in the OPTCL.…”
Section: Research Articlementioning
confidence: 99%
“…Comparing the microwave dried impregnated OPTCL to Rubber wood still a large gap for impact strength is observed. 24 This big gap is attributed to the brittleness of the PF resin which has been fully loaded in the OPTCL.…”
Section: Research Articlementioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] The liquefied wood-based novolac resins were reported to have a higher viscosity, a higher flow temperature than the commercial novolac resins. [9][10][11][12][13][14][15][16] The novolac resin made from oxalic acid-catalyzed phenol liquefied wood was found to follow an autocatalytic mechanism in the curing process. [11,12] However, there were few systematic studies on the effects of the type of acid catalysts on the properties of the liquefied biomass and the resulting liquefied biomass-based novolac resins.…”
Section: Introductionmentioning
confidence: 99%
“…The phenolated biomass material with molecular structures highly resembling novolac (Figure ) could be used directly as a novolac resin or it could be further reacted with formaldehyde under acidic condition to form thermoplastic resins without hydroxymethyl group in the molecular structure . Previous studies have shown that the molding products made from novolac resins containing phenol liquefied biomass materials including wood, bark, waste paper, lignin, and so on had comparable mechanical properties to those made from the commercial novolac resins. The liquefaction conditions, such as catalyst type and catalyst loading level, affected the liquefaction yield and properties of the liquefied products .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations